Structural design and performance analysis of hopping robot with buffer devices - WANG Jian; ZHANG Wenxiang; XU Chenglong; WANG Chenjie (Xibei Gongye Daxue Xuebao)
The existing hopping robot has large landing impact and poor landing stability. Therefore, a hopping robot with a new buffer device is designed. The anti-rotation mechanism in the buffer device is used to reduce the landing impact. The unidirectional bearing and damping ring are jointly employed to avoid the rebound of the hopping robot when the buffer device absorbs ground impact forces. Based on the principles of robotic mechanism, the main structure of the hopping robot is designed. Its motion principles are analyzed and its motion procedures are developed. The kinematics models of the hopping robot in its takeoff, flight and landing stages are established by using the D-H method. Its dynamic models in the takeoff and flight stages are studied according to the second-type Lagrange method. Its landing stability is analyzed based on the zero moment point (ZMP) theory and the ZMP trajectory plot is drawn. The hopping robot prototype is developed with the 3D printing technique and experiments on it are carried out. The study results significantly enhance the hopping stability of the hopping robot and reduce its landing impact.